2017
DOI: 10.7759/cureus.1595
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mental Health Service Utilization by Asian Americans and Non-Hispanic Whites versus Their Cardiovascular Care Utilization

Abstract: Introduction: This study will determine whether racial/ethnic disparities persist in various psychiatric disorders among Asian Americans.Methods: Secondary analyses of data from the second largest public health system in the US (total N=22294) were performed. Chi-squared statistics were used to compare the race for mental health service utilization for five psychiatric diagnoses. Cardiovascular care utilization by Asian Americans and non-Hispanic whites was used as a proxy for overall healthcare utilization ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Further studies should also utilize other search engines to replicate such results. As social media can bridge the gap between health care utilization and the Chinese over cultural barriers, future studies should examine the quality and content regarding dementia on social media [ 23 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should also utilize other search engines to replicate such results. As social media can bridge the gap between health care utilization and the Chinese over cultural barriers, future studies should examine the quality and content regarding dementia on social media [ 23 - 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having or reporting a mental health issue is a culturally stigmatizing issue in many AA communities, and these issues are often felt to be a sign of personal weakness which may bring dishonor or “shame” to a family’s reputation (Augsberger et al, 2015; Choi et al, 2016; Kim, 2011; Kim et al, 2015; Sue et al, 2012; Tse & Haslam, 2021; Woo, 2017; Yang et al, 2020). As such, the increase in reported rates of mental health distress might be due to a greater willingness to report psychological distress, or a true increase in psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…As a single group, Asian Americans (AA) have significantly lower utilization of mental health services than almost all other racial and ethnocultural groups, except for African Americans (Augsberger et al, 2015;Cheng et al, 2017;Kim, 2011;Lee et al, 2011;Sue et al, 2012;Tse & Haslam, 2021;Yang et al, 2020). AAs generally report lower prevalence of mental health disorders as compared to other racial groups (Alvarez et al, 2019;Cheng et al, 2017;Lee et al, 2011;Sue et al, 2012;Woo, 2017;Yang et al, 2020). Despite these reported values, however, mental health research among diaspora populations has highlighted that AA youth (15-24 years old) have the highest suicide rate for any racial group in the United States, Augsberger et al, 2015; Centers for Disease Control and Prevention [CDC/NCHS], 2018; Choi et al, 2016, and that multiple other AA subgroups, such as college students and the elderly, have disproportionately high rates of depression and suicidality (Cheng et al, 2017;Karasz et al, 2019;Kim et al, 2015;Lane et al, 2016;Sue et al, 2012;Woo, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Asian Americans make up 7% of the US population [1], mental health care services remain underutilized by this population. For example, in one study of populations who had undergone cardiovascular care, it was found Asian Americans were significantly less likely than non-Hispanic white populations to seek mental health care specifically for mood disorders including anxiety, depression and bipolar disorder, thought disorders including schizophrenia, as well as developmental conditions including intellectual disabilities [2]. In another study of utilization of mental health services based on 2012-2016 data from the National Survey on Drug Use and Health [3], Asian Americans were less likely than their white counterparts to have used mental health treatment in the last year.…”
Section: Commentarymentioning
confidence: 99%